The Effectiveness of the Circle Discussion Strategy in Developing Social Skills Among Seventh Grade Basic Students - Fattah, Nida Qahtan; Hussein Ibrahim, Azhar Ali; Omer, Othman Abdulkarim (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study aimed to investigate the effectiveness of the circle discussion strategy in developing social skills among seventh-grade basic students. An experimental design was employed with 57 female students divided into experimental (n=32) and control (n=25) groups. The experimental group was taught using the circle discussion strategy while the control group received traditional instruction. Data was collected using a social skills assessment measuring six key dimensions: cooperation and group work, communication, empathy and acceptance of others, school-home social skills, decision-making, and problem-solving. The experiment was conducted during the first semester of the 2024-2025 academic year in Zakho, Kurdistan Region, Iraq. Findings revealed statistically significant differences between the experimental and control groups in favor of the circle discussion strategy group. Analysis showed a large effect size (η²=0.496), confirming the strategy's substantial impact on developing students' social skills. The results suggest that structured circle discussion activities provide valuable opportunities for students to practice social skills in authentic contexts, reinforcing the importance of implementing interactive pedagogical approaches in middle school classrooms.